Answer:
13
Explanation:
This is my first time posting, so sorry if this isn't that clear.
Anyways:
We want to find the x-intercept, and the y-intercept. The x-intercept will always have 0 as y, and the y-intercept will always have 0 as x.
We can find the x-intercept by plugging in 0 as y. So:
x/4+0/12=1
x/4=1
x=4
a=4 (since a is equal to the x-intercept.)
We can find the y intercept by plugging in x as 0:
0/4+y/12=1
y/12=1
y=12
b=12
We can find the slope by using the equation y2-y1/x2-x1, but theres an easier way. Simplifying the original equation x/4+y/12=1 into y=--3x+12 immediatly gets us the slope of -3.
So, 12+4-3=13.
(In case you didn't know how I got y=-3x+12. This is how:
x/4+y/12=1
12(x/4+y/12)=1(12)
3x+y=12
y=-3x+12 )